Ionic liquids as active pharmaceutical ingredients - Ferraz, Ricardo (2011)
Ionic liquids (ILs) are ionic compounds that possess a melting temperature below 100 °C. Their physical and chemical properties are attractive for various applications. Several organic materials that are now classified as ionic liquids were described as far back as the mid-19th century. The search for new and different ILs has led to the progressive development and application of three generations of ILs: 1) The focus of the first generation was mainly on their unique intrinsic physical and chemical properties, such as density, viscosity, conductivity, solubility, and high thermal and chemical stability. 2) The second generation of ILs offered the potential to tune some of these physical and chemical properties, allowing the formation of “task-specific ionic liquids” which can have application as lubricants, energetic materials (in the case of selective separation and extraction processes), and as more environmentally friendly (greener) reaction solvents, among others. 3) The third and most recent generation of ILs involve active pharmaceutical ingredients (API), which are being used to produce ILs with biological activity. Herein we summarize recent developments in the area of third-generation ionic liquids that are being used as APIs, with a particular focus on efforts to overcome current hurdles encountered by APIs. We also offer some innovative solutions in new medical treatment and delivery options.